2013
DOI: 10.1093/mnras/stt412
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive abundance analysis of red giants in the open clusters NGC 2527, 2682, 2482, 2539, 2335, 2251 and 2266

Abstract: We have analyzed high-resolution echelle spectra of red giant members for seven open clusters in the Galactic anticentre direction to explore their chemical compositions. Cluster membership has been confirmed by radial velocity. The spread in temperatures and gravities being very small among the red giants, nearly the same stellar lines were employed for all stars thereby reducing the abundance errors: the errors of the average abundance for a cluster were generally in the 0.02 to 0.05 dex range. Our present s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 37 publications
5
64
1
Order By: Relevance
“…Table 8 summarizes the compositions of the local asso- Table 8. Mean elemental abundance ratios, [X/Fe], for Na to Eu for our sample of five associations, the thin disc mean abundances from Reddy et al (2012Reddy et al ( & 2013 and Reddy et al (2015) for OC giants, and Luck & Heiter (2007) for field giants, and Luck & Heiter (2005 and Bensby et al (2014) for field dwarfs, and Luck & Lambert (2011) ciations and the comparison samples mentioned above. Entries for the field dwarfs are taken from Luck & Heiter (2005 and from Benbsy et al (2014) with the constraint that [Fe/H] is in the range −0.10 to +0.10.…”
Section: Associations Clusters and Field Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 8 summarizes the compositions of the local asso- Table 8. Mean elemental abundance ratios, [X/Fe], for Na to Eu for our sample of five associations, the thin disc mean abundances from Reddy et al (2012Reddy et al ( & 2013 and Reddy et al (2015) for OC giants, and Luck & Heiter (2007) for field giants, and Luck & Heiter (2005 and Bensby et al (2014) for field dwarfs, and Luck & Lambert (2011) ciations and the comparison samples mentioned above. Entries for the field dwarfs are taken from Luck & Heiter (2005 and from Benbsy et al (2014) with the constraint that [Fe/H] is in the range −0.10 to +0.10.…”
Section: Associations Clusters and Field Starsmentioning
confidence: 99%
“…Over the last few years, several comprehensive highresolution studies of chemical abundances in the solar vicinity have been reported for field dwarfs (Edvardsson et al 1993;Reddy et al 2003Reddy et al , 2006Luck & Heiter 2005Bensby et al 2005Bensby et al , 2014, field giants (Mishenina et al 2006;Luck & Heiter 2007;Takeda et al 2008), and for open clusters (OCs; Friel et al 2002;Bragaglia et al 2008;Yong et al 2012;Reddy et al 2013Reddy et al , 2015, with the main goal of improving our knowledge of the chemical evolution of the Galactic disc.…”
Section: Introductionmentioning
confidence: 99%
“…The ages were calculated consistently, according to Carraro & Chiosi (1994). In the figures we include abundances obtained earlier (Mishenina et al 2013b(Mishenina et al , 2014 with measurements from other authors, for a number of OCs (D' Orazi et al 2009;Pancino et al 2010;Carrera & Pancino 2011;Maiorca et al 2011;D' Orazi et al 2012;Reddy et al 2012Reddy et al , 2013Bragaglia et al 2008;Yong et al 2005;Jacobson & Friel 2013) and the data for the thin disk stars were taken from the study by Mishenina et al (2013a).…”
Section: Etc) More In Generalmentioning
confidence: 99%
“…The sample red giant star HD 16771 analysed in this letter was selected as a part of the program dedicated to measure chemical abundances for red giants in open clusters (OCs; Reddy et al 2012Reddy et al , 2013Reddy et al , 2015. High-resolution (R ∼ 60 000) and high signal-to-noise ratio (S/N) optical spectra of HD 16771 were acquired during the night of 2013 November with the A&A 589, A57 (2016) Robert G. Tull coudé cross-dispersed echelle spectrograph (Tull et al 1995) at the 2.7-m Harlan J. Smith reflector of the McDonald observatory.…”
Section: Observations and Data Reductionmentioning
confidence: 99%